Open Versus Endovascular Stent Graft Repair of Abdominal Aortic Aneurysms: Do We Need More Randomized Clinical Trials?. (September 2014) - Firwana, Belal; Ferwana, Mazen; Hasan, Rim; Alpert, Martin A.; Faries, Peter; Dangas, George; Gluud, Christian
We performed an analysis to assess the need for conducting additional randomized controlled trials (RCTs) comparing open and endovascular aneurysm repair (EVAR) for abdominal aortic aneurysm (AAA). Trial sequential analysis (TSA) is a statistical methodology that can calculate the required information size of a meta-analysis and assess the risk of random errors similar to interim analysis in a single optimally powered trial. It helps to decide whether we have obtained sufficient evidence or whether further RCTs are required. For short-term mortality reintervention rates, TSA showed firm evidence that there would be no extra benefit in conducting more RCTs to detect the effectiveness of EVAR versus open repair. For long-term mortality, TSA revealed either inconclusive evidence to support or refute endovascular or open repair; so, further RCTs should be performed to investigate long-term, all-cause mortality after AAA repair.